2011
DOI: 10.1039/c1cc10691k
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Acinetobacter baumannii biofilm formation on a methacrylate polymer containing a 2-aminoimidazole subunit

Abstract: A polymeric composite containing a 2-aminoimidazole derivative was synthesized. It was found that this polymer was resistant to biofilm colonization by Acinetobacter baumannii, no leaching of the 2-aminoimidazole derivative was observed after 2 weeks of treatment with deionized water, and the resulting polymer was not hemolytic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Although a variety of antibacterial polymers has been reported, the ability of polymers to disrupt surface established bacterial biofilms have been scarce. Melander et al have shown methacrylate polymers containing 2-aminoimidazle subunit that inhibit A. baumannii biofilm formation [36]. Hedrick and co-workers demonstrated antimicrobial polymeric hydrogels that can disrupt bacterial and fungal biofilms [37].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Although a variety of antibacterial polymers has been reported, the ability of polymers to disrupt surface established bacterial biofilms have been scarce. Melander et al have shown methacrylate polymers containing 2-aminoimidazle subunit that inhibit A. baumannii biofilm formation [36]. Hedrick and co-workers demonstrated antimicrobial polymeric hydrogels that can disrupt bacterial and fungal biofilms [37].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…1a. This molecule has demonstrated great efficacy in affecting A. baumannii in both its biofilm and planktonic states 12,22 23. .…”
mentioning
confidence: 99%
“…These polymers also reduce the bacterial count in mice with chronic burn-wound infection [88]. Similar observation was seen with methacrylate polymers containing a 2-aminoimidazole subunit [112]. Chitosan nanoparticles act as adjuvant to carry outer membrane proteins of Acinetobacter and elicit excellent immune response in rats [92], indicating potential for developing a novel vaccine.…”
Section: Acinetobacter Biofilm Control Through Nanomaterialsmentioning
confidence: 77%
“…Properties of biocompatible polymers can also be harnessed for in vivo applications. However, very few reports are available on inhibition and disruption of Acinetobacter biofilms through polymers [92,112]. Maleic anhydride-based amphiphillic polymers, containing amide side chains, disrupt surface established A. baumannii biofilms.…”
Section: Acinetobacter Biofilm Control Through Nanomaterialsmentioning
confidence: 99%